EFEK RESIDU KOMPOS DAN UREA DENGAN APLIKASI KOMPOS KOTORAN KAMBING TERHADAP KETERSEDIAAN DAN SERAPAN N,P, K SERTA HASIL TANAMAN OKRA (Abelmoschus esculentus) PADA TANAH TERDAMPAK ERUPSI GUNUNG KELUD - Arinda Dining Atsari; Retno Suntari (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Mount Kelud is one of the most active volcanoes in Indonesia. Ash volcanic that released by Mount Kelud has some nutrients needed for plant, but requires a weathering process so as to provide nutrients in the soil. The soil that affected by Mount Kelud was given the addition of compost and urea fertilizer has residual effect for the next plant growth. This research was conducted in greenhouse of Agriculture Faculty, Brawijaya University from January until June 2017. This research used a completely randomized design with 5 treatments and 3 replications. The treatment consisted of A1: 2/3 soil residue (100% urea) + 1/3 goat manure compost; A2: 2/3 soil residue (100% chicken manure compost) + 1/3 goat manure compost; A3: 2/3 soil residue (100% cow manure compost) + 1/3 goat manure compost; A4: 2/3 soil residue (50% urea + 50% chicken manure compost) + 1/3 goat manure compost; A5: 2/3 soil residue (50% urea + 50% cow manure compost) + 1/3 goat manure compost. Variables of the observation were availability and uptake of NPK, plant height, number of leaves, number of pods, yield, and dry weight plant of okra. The results showed that compost residue and urea in the application of goat manure compost with ratio 2:1 had no effect in NPK availability on soil affected by Mount Kelud eruption. In plant’s parameter, there were effects on number of leaves at observation 12 weeks and P uptake, but no effect on N and K uptake, and okra’s yield.